Autoantibody profile in first trimester recurrent pregnancy loss - a tertiary care hospital study in North East India - Dutta BS; Talukdar PM; Dutta A; Sharma A; Choudhury SS; Baruah P; Punam K; Borah MS; Das P; Bayan M; Saikia TD; Saikia K; et al. (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Recurrent pregnancy loss (RPL), defined as the loss of two or more pregnancies before 20 weeks, is often linked to genetic, anatomical, endocrine, or autoimmune causes, though the reason remains unknown in about 50% of cases. This study aimed to assess the burden of autoimmune disease in RPL patients attending antenatal OPD and to profile associated autoimmune antibodies. A strong association was found between RPL and the presence of antiphospholipid (APA), antinuclear (ANA), and anti-thyroid peroxidase (Anti-TPO) antibodies. Methodology: 121 pregnant women in first trimester with a history of RPL were screened for Anti phospholipid, Anti Cardiolipin, Anti Thyroid Peroxidase and Anti Beta 2 Globulin 1 antibodies. The levels of Complement C3 and C4 were also evaluated. Results: 65(53.7%) cases were positive for either of the autoantibodies. Anticardiolipin IgG, Anticardiolipin IgM, Anti Phospholipid IgM, Anti Phospholipid IgG, Beta-2 glycoprotein IgM and Beta-2 glycoprotein IgG were found to be positive in 41(33.8%),3(2.4%), 10(8.2%), 4(3.3%),6(5%) and 1(0.8%) respectively. Anti TPO was positive in a significant number of participants 25(21%) despite having normal TSH levels. Complement C3 and C4 were however within normal ranges in all participants. Significant finding of the current study is that with one unit change in Anticardiolipin IgG, the level of C3 was increased by more than two times. Additionally mutual positive association was observed among the antibodies. Conclusion: Current study throws light on the prevalence of autoantibodies in recurrent pregnancy loss and opens avenues for further research to facilitate early management of RPL and better pregnancy outcomes.